Compression syndromes of the popliteal artery due to intramuscular ganglion cyst of the biceps femoris: A case report and literature review - Zheng, Kai; Yang, Wentao; Ren, Hualiang; Wang, Shengxing; Sun, Mingsheng; Zhang, Wangde; Li, Chunmin (Frontiers in Cardiovascular Medicine, 2022)
Intramuscular ganglion cyst(IMGC) is a very rare lesion with an unidentified pathogeny that originates within the muscle. We encountered a case of 49-year-old man who complained of intermittent claudication in the right lower limb for two months. An intramuscular ganglion cyst in the biceps femoris muscle was diagnosed and located by CTA and MRI, which compressed the popliteal artery and resulted in ischemia in the right lower limb. Six months after surgical resection, there was no recurrence of the cyst and the popliteal artery was patency. We describe this case with a review of the relevant literature.